2010
DOI: 10.1111/j.1744-6198.2010.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Effective and Ineffective Nurse-Physician Communication in Hospitals

Abstract: These themes may be useful in designing learning activities to promote effective interprofessional communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 27 publications
4
123
1
4
Order By: Relevance
“…Moreover, collaborative problem solving needs to be fostered (Robinson, Gorman, Slimmer, & Yudkowsky, 2010). It should be noted that most participants, when conveying a message, only communicate the content as they find it difficult to transmit their feelings in a message, and they sometimes forget to convey the request.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, collaborative problem solving needs to be fostered (Robinson, Gorman, Slimmer, & Yudkowsky, 2010). It should be noted that most participants, when conveying a message, only communicate the content as they find it difficult to transmit their feelings in a message, and they sometimes forget to convey the request.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Robinson et al (2010) using focus group interviews, nurses expressed that physicians often used rude and humiliating words which made them feel incompetent and intimidated. This display of unbecoming behaviors towards nurses resulted in a lack of and fear of communication with physicians (Robinson et al, 2010).It must be noted that effective communication is essential in building good working relationships between physicians and nurses (Petri, 2010) and also ensures that patient care is delivered correctly and timely (Sirota, 2007).However, a number of studies reported the communication between physicians and doctors tends to be unclear and imprecise (McCaffrey et al 2010;Rosenstein 2002;Weller et al;2011). The ambiguous communication resulted in delayed delivery of patient care and more frequent medical errors that ultimately jeopardized patients' safety (McCaffrey et al 2010;Rosenstein 2002).…”
Section: Recommendations To Improve Physician-nurse Collaborationmentioning
confidence: 99%
“…Apart from communication, respect, and trust, other factors affecting physician-nurse collaboration include understanding of professional roles, task prioritizing and equal power (Tang et al, 2013). Both Physicians and nurses recognize and value effective collaboration as an important element to come up with a quality patient care resulting to improved health outcomes for patients (Rosenstein 2002;Hughes & Fitzpatrick 2010;Robinson et al, 2010). In fact, collaboration and positive relationships between physician and nurse have been identified as major factors contributing to positive patient outcomes and quality patient care (Stein-Parbury, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The use of appropriate styles of communication also facilitates collaboration with colleagues and, in extreme cases, poor communication been linked to deaths of patients [7,8] . Effective nurse-doctor communication has been directly implicated in the maintenance of patient safety [9,10] . It is argued that such communication is further complicated in nursing with increased casualisation of the nursing workforce [11] .…”
mentioning
confidence: 99%